Exo- and endogenous factors of the development of organic production in ukraine - Trochymchyk А. (Land Management, Cadastre and Land Monitoring, 2024)
The article examines the restraining factors of the development of organic production in Ukraine. Two blocks of the main restraining factors that negatively affect the development and implementation of organic production are defined and summarized. Among the exogenous factors, the full-scale invasion of the aggressor country into Ukraine, as well as the price of organic products on the international market, are singled out. Endogenous restraining factors include legal, socio-economic, environmental, material and technical factors, as well as the irregularity of the lease model. It was determined that at the moment there is no clearly formed system of certification, standardization and labeling of organic products in Ukraine, but there are a number of legal acts, the norms of which create the basis for the development of the organic sphere. The legal, socio-economic, ecological and material-technical problems that restrain the development of organic production in Ukraine are identified and analyzed. It was determined that the existing system of land relations is built on the basis of a lease, and the production of organic products under lease conditions is risky, since a short-term lease contract is economically unprofitable for organic producers, because it is more aimed at the personal economic benefit of the owner of the land plot than the interest of the tenant in a good harvest. Another endogenous factor that restrains the development of organic farming in Ukraine is the manner in which the suitability of land plots for the production of organic products is established.